Correlation between Justice, Legal Certainty, and Benefit in Law Enforcement in Indonesia - Dwi Kurniawan, Itok (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Law is an instrument used to regulate human behavior in the order of social life in society so that it is in accordance with the values and norms that apply in society. Law as a norm has more stringent and coercive sanctions compared to other norms. Anyone who violates legal norms will certainly be subject to sanctions that cannot be contested by any party. The characteristics of strict and coercive legal norms and their sanctions are motivated by the fact that law has the main goal to achieve, namely justice, legal certainty and expediency. The method of writing this article uses a normative legal research method with a conceptual approach. The results of this study are that justice, legal certainty, and benefits must be realized in a harmonious and balanced manner in a law enforcement process. Equitable law enforcement will certainly create legal certainty, and will certainly bring benefits to justice seekers.